Wyzwania okresu dorastania u osób homoseksualnych w świetle teorii rozwoju biopsychospołecznego Erika Eriksona - Bandel, Jerzy; Wycisk, Jowita (Człowiek i Społeczeństwo, 2021)
Classical concepts of human development elaborated in the 20th century do not take into consideration the normative development of homosexual people. On the other hand, the depathologization of homosexuality has resulted in an increase of knowledge about gays’ and lesbians’ performance and health. The process of homosexual identity formation, usually beginning in adolescence, has been recognized and well described in the field of psychology. However, this knowledge is rarely integrated with general theories of human development. The article presents the developmental challenges of adolescence and points out the limitations and possibilities of Erikson’s theory in incorporating the experiences of homosexual adolescents. The authors discuss the specific difficulties minority adolescents face growing up in a heteronormative culture and the main stages of homosexual identity formation. The article ends with a reflection on the possibility of integrating the concept of homosexual identity development with Erik Erikson’s theory of identity crisis and its potential solutions in adolescence.